Customers' judgments and misjudgments of corporate responsibility communication: A cross‐country investigation of the effects on confidence and trust within the banking sector. Issue 2 (10th January 2018) - Civera, Chiara; Casalegno, Cecilia; Mosca, Fabrizio; Maple, Peter
Abstract: Customers' judgment of corporate responsibility (CR) communication and the effect on confidence and trust as interlinked paradigms are intriguing areas of investigation from both theoretical and empirical perspectives. This research aims to clarify the nature of effective CR communication toward customers by identifying situations of over‐ and undercommunication of CR that might cause misjudgments and therefore lower the level of confidence among customers. The study also provides insights to better explain the link between confidence and trust related to customers' perceptions of CR communication and compares different judgments and misjudgments regarding the banking industries in Italy and the United Kingdom. The study adopts real and fictitious bank case studies to conduct focus groups investigations of 160 millennial customers' perceptions of CR communication and how it affects their level of confidence. The findings highlight the role of trust in making independent judgments on CR communications. Some similarities and slight differences in the impact of CR communication on confidence emerge between the countries and greatly depend on the customers' level of trust in real banks and the influence of the industry effect characterizing the banking sector. This study provides fertile ground for future research into the implementation of a more effective and balanced CR communication strategy to increase customers' confidence and into the understanding of which communication drivers, apparently independent of CR, affect trust in the long term.